Você está na página 1de 4

Quantum Mechanics Demystified

Chapter 7 Corrections
Page 183

Should be

“We can use these results to write the matrix representation of A”

Page 187:

z− z 
2

“Recalling that zz * = Re ( z ) + Im ( z ) ≥ Im ( z ) = 
2 2 2

 2i 

Should be:

2
 z − z* 
zz = Re ( z ) + Im ( z ) ≥ Im ( z )
2 2 2
*
= 
 2i 

Page 194 Solution to Example 7.6

[ A, B ] ∑ bn nBb −1
n =0

Should be:

[ A, B] ∑ bn nB n −1

n= 0

Page 196:

Should be:

“we obtain the representation of Ψ in the”

Page 199:
a 2 ∞ 2 2 − ax 2 a 2 ∞ − ax 2
h ∫ a x e dx −
π ∫−∞
=− h ae dx
π −∞

a 2  2 Γ (1 / 2)  a 2 π 
=− h a − h a
π 2a3 / 2 

π  a 
  

a 2 π
=− h − h2 a
π 2a 3/2

h 2a h 2a
=− − h 2a =
2 2

Should be:

a 2 ∞ 2 2 − ax 2 a 2 ∞ − ax2
h ∫ a x e dx +
π ∫−∞
=− h ae dx
π −∞

a 2  2 Γ (1 / 2)  a 2 π 
=− h a 3/2 
+ h a 
π  2a  π  a 

a 2 π
=− h + h2 a
π 2a 3/2

h 2a h 2a
=− +h a=
2

2 2

Page 200:

df
= iλ dϕ ⇒ ln = iλϕ + C
f

df
= iλ dϕ ⇒ ln f = i λϕ + C
f
Quantum Mechanics Demystified
Chapter 8 Corrections
Page 207:
 0 X 0 0 X 1   01 0 0   1 0
X = = =
 1X 0 1 X 1   11 1 0   0 1 

Should be:

 0 X 0 0 X 1   01 0 0   0 1
X = = =
 1X 0 1 X 1   11 1 0   1 0 

Page 210 solution to Example 8.3:

h h
λ −λ
2 Should be det 2
det
h h
λ −λ
2 2

Page 213:
“where the Φ1 constitutes an orthonormal basis”

“where the Φ i constitutes an orthonormal basis”

Page 216:
 9  1  1   49  63 21
H = E   + 2E   + 3E   + 4E   = E= E
 60   60   60   60  60 20

 9  1  1   49  210 7
H = E   + 2E   + 3E   + 4E   = E= E
 60   60   60   60  60 2

“Where each of those eigenvectors corresponds to the same eigenvector” should read
“Where each of those eigenvectors corresponds to the same eigenvalue”
Quantum Mechanics Demystified
Chapter 9 Corrections
Page 246:

16u 4 − 48u 2 −12 should be 16u 4 − 48u 2 + 12

Page 252:

mω  ip  1 mω  i2 p  2
=  mω  = i p should be =  mω  = i p
2h   2hmω 2h   2hmω

Page 253:

hω  1
H= 1 + 2a† a  = hω  a †a + 
4  2

Should be:

hω hω  † 1
H= 1 + 2a †a  = a a + 
4 2  2